Chocolates and ‘Legrias’: Dilemma of the Best Sales Channel - Silva,Andre Luiz Barbosa da (2021)
ABSTRACT This teaching case aims to understand the challenges between opening distribution channels and new products. The report involves a small Brazilian chocolate factory. It presents the structuring, production processes, brand concept, formation of sales prices, and the choice of distribution channels in COVID-19 times. The company faced challenges in the market for presenting products with low adherence to distribution channels, high costs and price, and an inadequate brand positioning, resulting in low sales. After repositioning itself with a new brand and price concept, the case raises the dilemma: What is the best distribution channel during the crisis period caused by COVID-19 for the newly restructured company? The pedagogical objectives are focused on the analysis of alternatives in the choice of distribution channels, considering the implementation challenges, the transaction costs for products at an early stage, and the scenario of uncertainties resulting from the pandemic, as well as the application of sales channel concepts and distribution. The case can be applied in undergraduate and MBA courses in the management area and is recommended to encourage students to reflect on the structure and challenges of implementing small entrepreneurs’ distribution channels.